Senofilcon A contact lenses and UV-blocking spectacle lenses provide equal protection against UV-induced expression of p53 and caspase-3 in lens epithelial cells - Ni Putu Ayu Reza Dhiyantari; Nurwasis Nurwasis; Dicky Hermawan; Made Dessy Gangga Ayu Cinthiadewi; Rifat Nurfahri (Journal of Advanced Biotechnology and Experimental Therapeutics)
The importance of safe and effective efforts to prevent cataract incidence, one of which is by providing direct ultraviolet light protection to the eye. The objective of this study was to compare the effectiveness of UV-blocking spectacles and Senofilcon A contact lenses in protecting against UV-B-induced cataract. The associated lens damage was measured through the expression of P53 and caspase-3 in lens epithelial cells. Rats were exposed to direct UV-B irradiation from a UV-B lamp positioned 18 cm anterior to the right eye for 30 minutes, with an average irradiation energy of 6.5 kJ/m². Rats were irradiated without protection (P1), with UV-blocking spectacles protection (P2), and Senofilcon A contact lens protection (P3). Rats were euthanized, and eyes were enucleated on day 3 after UV-B exposure. UV-B exposure to unprotected eyes causes increased expression of P53 as a marker of DNA damage and increased caspase-3 as an executor of apoptosis in the lens epithelial cells. Immunohistochemistry was utilized to assess the expression of p53 and caspase-3 in the lens epithelial cells. The UV-B irradiation group showed the highest mean expression of P53 and caspase-3. The expression of p53 in both protection groups was significantly lower compared to the unprotected radiation groups (p =0.042, p =0.001). Similar results were obtained in the expression of caspase-3 of both protection groups compared to unprotected radiation (p = 0.017; p =0.002). The expression of p53 and caspase-3 was not significantly different when comparing the two protection groups (p =0.386, p =0.158). UV-blocking spectacles and Senofilcon A contact lenses provided equally effective protection in preventing UV-B radiation-induced P53 and caspase-3 expression. Finally, the data suggest that both of these protective measures can be employed as a means of preventing UV-B-induced cataract. [ J Adv Biotechnol Exp Ther 2025; 8(2.000): 370-382]